Transformative trajectories: Pls-sem analysis of factors influencing emerging technologies in construction adoption in Malaysia - Fakhira, Khudzari; Ahmad Tarmizi, Haron; Ayer, Steven K.; Abdul Rahimi, Abdul Rahman (International Council for Research and Innovation in Building and Construction, 2025)
The rapid development and integration of emerging technologies in construction (ETC) have revolutionized traditional processes, workflows, and management systems. Despite these advancements, the adoption of these technologies varies widely across organizations and projects, posing challenges to the industry. This study aims to identify the key factors influencing ETC adoption and develop a structural equation model to analyze their relationships, using Malaysia as a case study. Through a systematic literature review, relevant factors were identified, followed by a survey with 147 industry professionals to evaluate the importance of the factors. Data were analyzed using agreement analysis, mean score ranking, exploratory factor analysis (EFA), and partial least squares structural equation modeling (PLS-SEM). The analyses identified 14 key factors, which can be further classified into three underlying constructs: organizational resources, organizational goals, and organizational strategy. Notably, the findings suggest that only organizational strategy plays a significant role in ETC adoption decisions. Consequently, strategic alignment should be a primary consideration for organizations planning to adopt ETC. This study contributes to the literature by providing a comprehensive analysis of the factors influencing ETC adoption. Researchers and industry professionals can leverage these insights to develop effective strategies that enhance ETC adoption rates, driving innovation and efficiency in the construction industry.